Pathologic staging changes in oral cavity squamous cell carcinoma: Stage migration and implications for adjuvant treatment. Issue 17 (15th May 2019) - Lee, Nicholas C. J.; Eskander, Antoine; Park, Henry S.; Mehra, Saral; Burtness, Barbara A.; Husain, Zain
Abstract : Background: The eighth edition of the AJCC Cancer Staging Manual (AJCC 8) incorporates depth of invasion (DOI) into the pathologic tumor (pT) classification and pathologic extranodal extension (pENE) into the pathologic nodal (pN) classification for oral cavity squamous cell carcinoma (OCSCC). This study evaluated the incidence and prognostic importance of stage migration as a result of these changes in the AJCC 8 staging system. Methods: From the National Cancer Database, cohorts were identified from patients with OCSCC undergoing definitive surgery between 2004 and 2013 for pT (n = 7184), pN (n = 13, 627), and pathologic stage (pStage) analysis (n = 5580). Results: DOI and pENE were prognostic in all groups except for pN3 according to the seventh edition of the AJCC Cancer Staging Manual (AJCC 7). Upstaging was seen in 12.4% of patients for the pT classification, in 13.3% for the pN classification, and in 24.8% for the overall pStage grouping. Notably, upstaging led to similar or improved 5‐year overall survival (OS) for every AJCC 8 pT/N classification except pStage IVB. Patients with AJCC 7 pT1 tumors that were upstaged to AJCC 8 pT3 tumors had improved OS in comparison with the remainder of the pT3 group (71.7% vs 43.7%; P  < .0001). A multivariable analysis of upstaged pT3N0 patients demonstrated a reduced risk of death with the receipt of postoperative radiotherapy (PORT; hazard ratio, 0.56; 95% confidence interval, 0.33‐0.95; P  = .03). Conclusions: Upstaging is common in AJCC 8, and patients with upstaged tumors demonstrate improved survival; these factors should be kept in mind when one is interpreting data with the new staging system. PORT may reduce deaths among newly upstaged pT3N0 patients, and further study is needed in this area. Abstract : Upstaging is common in the eighth edition of the AJCC Cancer Staging Manual, and patients with upstaged tumors demonstrate improved survival; these factors should be kept in mind when one is interpreting data with the new staging system. Postoperative radiotherapy may reduce deaths among newly upstaged pT3N0 patients, and further study is needed in this area.